Spherocytic shift of red blood cells during storage provides a quantitative whole cell–based marker of the storage lesion. Issue 4 (1st February 2017) - Roussel, Camille; Dussiot, Michaël; Marin, Mickaël; Morel, Alexandre; Ndour, Papa Alioune; Duez, Julien; Le Van Kim, Caroline; Hermine, Olivier; Colin, Yves; Buffet, Pierre A.; Amireault, Pascal
Abstract : BACKGROUND: Storage lesion may explain the rapid clearance of up to 25% of transfused red blood cells (RBCs) in recipients. Several alterations affect stored RBC but a quantitative, whole cell–based predictor of transfusion yield is lacking. Because RBCs with reduced surface area are retained by the spleen, we quantified changes in RBC dimensions during storage. STUDY DESIGN AND METHODS: Using imaging flow cytometry we observed the dimension and morphology of RBCs upon storage, along with that of conventional biochemical and mechanical markers of storage lesion. We then validated these findings using differential interference contrast (DIC) microscopy and quantified the accumulation of microparticles (MPs). RESULTS: Mean projected surface area of the whole RBC population decreased from 72.4 to 68.4 µm 2, a change resulting from the appearance of a well‐demarcated subpopulation of RBCs with reduced mean projected surface (58 µm 2, 15.2%‐19.9% reduction). These "small RBCs" accounted for 4.9 and 23.6% of all RBCs on Days 3 and 42 of storage, respectively. DIC microscopy confirmed that small RBCs had shifted upon storage from discocytes to echinocytes III, spheroechinocytes, and spherocytes. Glycophorin A–positive MPs and small RBCs appeared after similar kinetics. CONCLUSION: The reduction in surface area of small RBCs is expected to induce their retention by the spleen. We propose that small RBCs generated by MP‐induced membrane loss are preferentially cleared from the circulation shortly after transfusion of long‐stored blood. Their operator‐independent quantification using imaging flow cytometry may provide a marker of storage lesion potentially predictive of transfusion yield.